PEDAGOGICAL PRACTICES FOCUSED ON CHILDREN WITH ASD (PRÁXIS EM SAÚDE, 2026)
Autism Spectrum Disorder (ASD) affects areas such as social skills, communication, and behavior, making the learning process a challenge for educators. This study aimed to analyze works that address pedagogical practices focused on students with ASD, seeking to understand strategies that promote the inclusion and development of these students. The research is justified by the interest in deepening knowledge in the field of special education and understanding how inclusion occurs in mainstream schools. The study is bibliographic in nature, based on books, scientific articles, and specialized publications on the subject.
Keywords: Pedagogical Practice; Learning; Autism Spectrum Disorder